2002
DOI: 10.1042/bj3640255
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of hELD/OSA1, a novel BRG1 interacting protein

Abstract: A highly conserved multisubunit enzymic complex, SWI/SNF, participates in the regulation of eukaryote gene expression through its ability to remodel chromatin. While a single component of SWI/SNF, Swi2 or a related protein, can perform this function in vitro, the other components appear to modulate the activity and specificity of the complex in vivo. Here we describe the cloning of hELD/OSA1, a 189KDa human homologue of Drosophila Eld/Osa protein, a constituent of Drosophila SWI/SNF. By comparing conserved pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 79 publications
2
38
0
Order By: Relevance
“…2b and c). This finding is consistent with those of a report that noted the abundance of this protein in brain extract and its low level in HeLa cells (10).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…2b and c). This finding is consistent with those of a report that noted the abundance of this protein in brain extract and its low level in HeLa cells (10).…”
Section: Resultssupporting
confidence: 83%
“…While this work was in progress, two labs reported partial cDNA sequences of BAF250b (10,12). Their reported proteins are 1,486 and 1,740 amino acids long, respectively, whereas BAF250b described here is 1,956 amino acids long.…”
Section: Resultsmentioning
confidence: 99%
“…BAF250A (also known as OSA1 and p270/ARID1A) is encoded by ARID1A, whereas BAF250B (OSA2) is encoded by ARID1B (Hurlstone et al, 2002;Wang et al, 2004b). In addition to the ARID domains, BAF250s also contain EHD1 and EHD2 domains, which map to the C termini and mediate protein binding (Hurlstone et al, 2002). BAF250A has been linked to the functions of steroid receptors (Inoue et al, 2002).…”
Section: Swi/snf Subunits and Their Role In Gene Regulation And Cancermentioning
confidence: 99%
“…Missense mutations in this domain are likely to disrupt the DNA-binding ability of ARID1B and compromise the function of the BAF complex. DUF3518 is approximately 260 amino acids long and biochemical studies have indicated that the domain interacts with the helicase subunits BRG1 and BRM in BAF complexes (24,35). Therefore, missense mutations in DUF3518 are likely to disrupt the interaction between ARID1B, BRG1, and BRM.…”
Section: Impact Of Arid1b Mutationsmentioning
confidence: 99%